2021
DOI: 10.1002/14651858.cd013579.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for progression or recurrence of glioblastoma: a network meta-analysis

Abstract: BackgroundGlioblastoma (GBM) is a highly malignant brain tumour that almost inevitably progresses or recurs a er first line standard of care. There is no consensus regarding the best treatment/s to o er people upon disease progression or recurrence. For the purposes of this review, progression and recurrence are considered as one entity. ObjectivesTo evaluate the e ectiveness of further treatment/s for first and subsequent progression or recurrence of glioblastoma (GBM) among people who have received the stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 167 publications
1
55
0
3
Order By: Relevance
“…This reflects the predominance of UK and European responders to our questionnaire. Single agent Lomustine at progression is most commonly used in North America and is the most common comparator for novel agents in randomised controlled trials of progression [31]. Any surgical trial will need to account for or control these variations in practice.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the predominance of UK and European responders to our questionnaire. Single agent Lomustine at progression is most commonly used in North America and is the most common comparator for novel agents in randomised controlled trials of progression [31]. Any surgical trial will need to account for or control these variations in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a network meta-analysis demonstrated that lomustine appears to be the most effective chemotherapy treatment and other combination therapies tested (BEV monotherapy, BEV plus lomustine, bevacizumab and irinotecan, regorafenib, TMZ plus Depatux-M, and fotemustine) had a higher risk of serious side effects for treatment of first recurrence of GBM [161].…”
Section: Development Of New Drugs For Glioblastoma Treatmentmentioning
confidence: 99%
“…Such shortcomings in clinical trial design and therapeutic evaluation should now be behind us, and the stage is ready for more rapid drug discovery in “window of opportunity” studies and adaptive platform clinical trial designs. It remains implausible to think that one single targeted therapy will move the needle in the overall survival from recurrent GBM [ 258 ]; but our field has made little effort to understand whether specifically defined subgroups of patients may demonstrate benefit despite negative phase III results. The proverbial “throwing out the baby with the bathwater” approach to failed clinical trials should not be an acceptable outcome of these efforts.…”
Section: Future Directionsmentioning
confidence: 99%